Optimasi Waktu Pemasakan Bandeng Presto - Suwedo Hadiwiyoto; Sri Naruki (agriTECH, 1999)
A study of the optimation of processing time to produce highly acceptable "bandeng presto" was conducted by cooking '5. 1 of milidish (Chanos chanos) at 121°C and charatecterization of H. I the physical and chemical properties 15psi. Increasing cooking time gave softer fishbone and meat as shown by increasing water holding capacity (WHC) and score given by panelists. Cooking at high temperature decreased protein solubility, however by increasing time of cooking result in increasing in protein solubility The preferences of panelists were affected by appearance and flavour "bandeng presto" products. Cooking of milkfish aT121Â°C and 15psi for 60 minutes produced highly acceptable "bandeng presto" containing about 3% salt base on appearance, bone and meat softness, and flavour